Pengaruh Work Life Balance, Stres Kerja dan Lingkungan Kerja Terhadap Kinerja Pegawai BMT Al Hikmah Semesta - Intan Khoirun Nisa; Ahmad Fauzan Mubarok; Cahyaning Budi Utami (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the effect of work-life balance, work stress, and work environment on employee performance at BMT Al Hikmah Semesta. A quantitative approach was used involving 41 respondents who were selected as samples. Primary data collection was conducted through observation and structured questionnaires distributed through the Google Forms platform. Descriptive statistical analysis, validity and reliability tests, classical assumption tests, and hypothesis testing were conducted to test the relationship between variables. The results showed that work-life balance and work environment partially have a positive and significant influence on employee performance. However, work stress does not show a significant influence on employee performance. Furthermore, simultaneously, work-life balance, work stress, and work environment together have a positive and significant influence on the performance of BMT Al Hikmah Semesta employees. These findings provide important implications for BMT Al Hikmah Semesta management in an effort to improve employee performance through managing work-life balance, reducing work stress, and creating a conducive work environment